2019
DOI: 10.4018/ijom.2019100101
|View full text |Cite
|
Sign up to set email alerts
|

Does Gender, Age and Income Moderate the Relationship Between Mobile Banking Usage and Loyalty?

Abstract: This article aims to determine the moderating role of demographics gender, age and income on the relationship between mobile banking (m-banking) usage and loyalty towards the service. A sample of 524 m-banking users from the state of Punjab in India was used to understand the interaction of this relationship. The collected data was then analyzed through moderated multiple regression analysis using dummy variables. Results of the study reveal that among the three demographics, gender and age moderate the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…However, not all users are proficient in this language, which results in resistance and low adoption. • Gender -Gender is an essential moderating variable in adopting mobile business applications (Vasudeva & Chawla, 2019). • Social influences -Hong (2019) found that social influences have a significant positive relationship with the intent to use mobile banking.…”
Section: Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, not all users are proficient in this language, which results in resistance and low adoption. • Gender -Gender is an essential moderating variable in adopting mobile business applications (Vasudeva & Chawla, 2019). • Social influences -Hong (2019) found that social influences have a significant positive relationship with the intent to use mobile banking.…”
Section: Securitymentioning
confidence: 99%
“…Information and reassurances provided by individuals surrounding the consumers could improve awareness and consumer intentions towards mobile technology (Baabdullah & Alalwan, 2019). • Age -Age was used as a moderating role in various mobile banking studies (Chawla & Joshi, 2018;Chaouali & Souiden, 2019;Vasudeva & Chawla, 2019). Consumers are inspired to use mobile banking based on their needs which is likely to change as they age (Trabelsi-Zoghlami et al, 2018).…”
Section: Securitymentioning
confidence: 99%
“…Correlating with the increase in numbers, recent literature has also paid particular attention to comprehending MB technology (Alkhaldi and Kharma, 2019;Changchit et al, 2020;Chawla and Joshi, 2019;Chien et al, 2018;Choudrie et al, 2018;Foroughi et al, 2019;Merhi et al, 2020;Picoto and Pinto, 2021;Singh and Srivastava, 2020;Souiden et al, 2021;Vasudeva and Chawla, 2019). It is the service channel for banking whose way was paved by the advances in digital technologies and smartphones and their widespread use.…”
Section: Consumer Compatibility and Bank Reputation 417mentioning
confidence: 99%
“…, 2020; Picoto and Pinto, 2021; Singh and Srivastava, 2020; Souiden et al. , 2021; Vasudeva and Chawla, 2019). It is the service channel for banking whose way was paved by the advances in digital technologies and smartphones and their widespread use.…”
Section: Introductionmentioning
confidence: 99%
“…Variable age is considered an important factor affecting the online behavior of an individual (Rialti et al, 2019;Sheldon et al, 2021). Marketing studies highlight the importance of age in technology acceptance and reveal that younger generations mostly have a positive attitude toward the adoption of new technology (Nash, 2019;Vasudeva & Chawla, 2019) and this may also be true in the case of mobile social media. There is a digital divide in technology usage among the generations in terms of age (Berezan et al, 2018;Friemel, 2016).…”
Section: Introductionmentioning
confidence: 99%